Advances and challenges in uncovering cold tolerance regulatory mechanisms in plants. Issue 4 (25th February 2019) - Ding, Yanglin; Shi, Yiting; Yang, Shuhua
Abstract : Contents Summary I. Introduction II. Cold stress and physiological responses in plants III. Sensing of cold signals in plants IV. Messenger molecules involved in cold signal transduction V. Cold signal transduction in plants VI. Conclusions and perspectives Acknowledgements References Summary: Cold stress is a major environmental factor that seriously affects plant growth and development, and influences crop productivity. Plants have evolved a series of mechanisms that allow them to adapt to cold stress at both the physiological and molecular levels. Over the past two decades, much progress has been made in identifying crucial components involved in cold‐stress tolerance and dissecting their regulatory mechanisms. In this review, we summarize recent major advances in our understanding of cold signalling and put forward open questions in the field of plant cold‐stress responses. Answering these questions should help elucidate the molecular mechanisms underlying plant tolerance to cold stress.